2007
DOI: 10.1021/jo061697v
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Equilibria in Formic Acid and the Adduct of Formic Acid and Hexafluoroacetone, HCO2C(CF3)2OH

Abstract: Low-temperature 1H and 13C NMR spectra of formic acid (1) showed separate signals for the E and Z conformations in solvents containing a hydrogen bond acceptor, dimethyl ether. The population of E-1 (6.2% in 3:1:1 CHClF2/CHCl2F/(CH3)2O) was larger than that for 13C-labeled methyl formate in the same solvent (0.2%), which indicated that the relative populations are not determined by steric effects. The free-energy difference between the E and Z conformations of 1 was 0.9 kcal/mol. In a 1:3 CD2Cl2/(CH3)2O solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In accordance with the previous studies of formic acid and acetic acid, the cis conformation predominates in most of the cases. This is mainly attributed to the less dipole interaction between the carboxylic C−O bond and the O−H bond in the cis conformation, ,, which stabilizes the cis conformation and results in the lesser dipole moment of the cis conformer (see below).…”
Section: Resultssupporting
confidence: 92%
“…In accordance with the previous studies of formic acid and acetic acid, the cis conformation predominates in most of the cases. This is mainly attributed to the less dipole interaction between the carboxylic C−O bond and the O−H bond in the cis conformation, ,, which stabilizes the cis conformation and results in the lesser dipole moment of the cis conformer (see below).…”
Section: Resultssupporting
confidence: 92%
“…While much interest has therefore focused on the energy difference involved, experimental data seem to be derived entirely from formic acid, and computational results have seldom extended much further. For the most part, ÁG syn/anti values found for vapor-phase formic acid lie in the 8.5±16.5 kJ mol À1 range (Miyazawa & Pitzer, 1959;Lide, 1964Lide, , 1966Hocking, 1976); however, Pawar et al (2007) have recently reported a ÁG syn/anti for formic acid of ca 3.8 kJ mol À1 in a solution that permitted hydrogen bonding but suppressed dimerization. The computational values for ÁG syn/anti generally fall in the range 19± 26.5 kJ mol À1 (Radom et al, 1972;Allinger & Chang, 1977;Peterson & Csizmadia, 1979;Wiberg & Laidig, 1987), and the few values calculated for acetic and propionic acids are higher than the formic acid values by a few kJ mol À1 .…”
mentioning
confidence: 99%
“…C‐cyclization and oxonium‐induced ring opening of the pyran to intermediate 15 is supported by the isolation of type A scaffold (±)‐ 14 from the reaction mixture. We propose that addition of formic acid to the strained bridgehead ketone of 15 may lead to formation of hemiketal 16 [8i, 10a,c] . Following cyclization to the bridged oxetane 17 , Grob‐type fragmentation [24] may provide product 12 .…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to other Brønsted acids, formic acid has inherent properties that may be responsible for promoting cyclization to the clusianone core: [8i, 10] 1) formic acid may stabilize carbocations by solvation effects as evidenced by formate adducts of 1,1‐disubstituted olefins; [10b] 2) formate adducts of strained bridgehead ketones may facilitate cyclizations that would otherwise be less feasible [8i, 10a,c] . In this study, diversity‐oriented synthesis (DOS) [11] of synthetic acylphloroglucinol scaffolds (SASs) is described using formic acid in comparison to other Brønsted acids for promoting unique cyclizations and rearrangements, and multiplexed‐activity profiling (MAP) is used to evaluate activities in diverse biological pathways (Figure 1 c).…”
Section: Introductionmentioning
confidence: 99%